Silicon nitride core-shell coated powder, ceramic prepared from silicon nitride core-shell coated powder and preparation method of ceramic

By using titanium nitride as the second cladding layer in the silicon nitride ceramic material to form a uniform three-dimensional network structure, the brittleness and electrical insulation problems of the silicon nitride ceramic material are solved, and the mechanical properties optimization and electromagnetic of the ceramic are achieved Improved performance and suitable for applications in high demand areas.

CN119409513APending Publication Date: 2025-02-11LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411252749.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Due to the limitations of intrinsic brittleness and electrical insulation, existing silicon nitride ceramic materials are difficult to be applied in high-demand fields, and the network structure of the existing preparation methods is uneven and the preparation process is complex, making it difficult to achieve industrialization.

Method used

Silicon nitride core-shell coating powder is used, and a ceramic material with a double-layer structure is formed by dry mixing and SPS sintering technology. Titanium nitride is used as the second cladding layer to form a uniform three-dimensional network structure.

Benefits of technology

It improves the fracture toughness and bending strength of ceramics, optimizes the electromagnetic performance, solves the problems of uneven network structure and complex preparation process, and improves the possibility of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409513A_ABST
    Figure CN119409513A_ABST
Patent Text Reader

Abstract

The invention provides silicon nitride core-shell coated powder, ceramic prepared from the silicon nitride core-shell coated powder and a preparation method of the silicon nitride core-shell coated powder, the silicon nitride core-shell coated powder is of a double-layer structure and is composed of silicon nitride, a sintering aid and titanium nitride, the silicon nitride serves as a matrix, the surface of the matrix is coated with the sintering aid, the surface of the sintering aid is coated with the titanium nitride, and the surface of the sintering aid is coated with the titanium nitride. The preparation method comprises the following steps: mixing spherical silicon nitride subjected to spray drying with a sintering aid by a dry method, and pre-sintering, so as to obtain silicon nitride matrix coated powder; and carrying out dry mixing on the titanium nitride and the silicon nitride matrix coated powder, and sintering to prepare the ceramic with the uniform network structure. Silicon nitride is used as a matrix, and a uniform three-dimensional network structure is introduced into the matrix, so that the mechanical property and the electromagnetic property of the ceramic material are optimized at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides silicon nitride core-shell coated powder and ceramics prepared therefrom and a preparation method thereof, and relates to the technical field of ceramic materials. Background Art

[0002] High-performance structural ceramics play a vital role in modern industry, and are particularly suitable for applications in high temperature, high pressure and highly corrosive environments. Silicon nitride (Si3N4), as a typical high-performance ceramic material, has attracted much attention due to its excellent mechanical properties, high temperature resistance and chemical stability. However, with the continuous advancement of technology, the performance requirements for silicon nitride ceramics are becoming increasingly higher. Silicon nitride ceramics are limited in their application in certain high-demand fields due to their intrinsic brittleness and electrical insulation. Therefore, further improving the toughness of silicon nitride ceramics and optimizing their electromagnetic properties have become a hot topic and difficulty in current research.

[0003] The technical problems of poor toughness and insulation of silicon nitride-based ceramic materials can be improved by introducing a hard phase with conductive properties into the silicon nitride matrix. The second phase currently constructed by ball milling is evenly distributed in the matrix and is difficult to fully play a crack barrier role. At the same time, the isolated distribution of the conductive phase is difficult to break through the conductive threshold. The method of constructing a network structure preparation has the problems of uneven network structure and overly complicated preparation process, which not only limits the optimization of ceramic performance, but also greatly increases the production cost, making it difficult to achieve industrialization.

[0004] Therefore, it becomes very important to prepare silicon nitride composite ceramics with excellent performance and uniform network structure distribution in a relatively simple way. Summary of the invention

[0005] The invention provides silicon nitride core-shell coated powder and ceramics prepared therefrom and a preparation method thereof, which solve the technical problems of uneven distribution of the network structure of the coating layer and complicated preparation method in the prior art.

[0006] The present invention is implemented as follows: the silicon nitride core-shell coated powder has a double-layer structure, with silicon nitride as the matrix, a sintering aid as the first coating layer, and titanium nitride coated on the surface of the sintering aid by dry mixing as the second coating layer.

[0007] As further preferred, the mass ratio of the titanium nitride to the silicon nitride having the first coating layer is 5-30:70-95.

[0008] As a further preference, the mass ratio of the titanium nitride to the silicon nitride having the first coating layer is 10:90.

[0009] As a further preference, the mass ratio of the silicon nitride to the sintering aid is 95:5.

[0010] As a further preference, the median diameter of the silicon nitride is 75 μm, and the average diameter of the titanium nitride is 50 nm.

[0011] As a further preference, the sintering aid consists of Al2O3 and Y2O3 in a mass ratio of 2:3.

[0012] The present invention also provides a ceramic prepared by sintering silicon nitride core-shell coated powder.

[0013] The present invention also provides a method for preparing ceramics, comprising the following steps:

[0014] (1) dry-mixing the spray-dried spherical silicon nitride powder with a sintering aid and then pressurelessly sintering to obtain a silicon nitride matrix powder having a first coating layer;

[0015] (2) dry-mixing the titanium nitride powder with the silicon nitride matrix powder having the first coating layer obtained in step (1) to obtain the silicon nitride matrix powder having the second coating layer;

[0016] (3) Sintering the silicon nitride matrix powder having the second coating layer obtained in step (2).

[0017] As a further preference, the process parameters of the dry mixing in step (1) and step (2) are: rotation speed 80-100 rpm, mixing time 8-12 h.

[0018] As a further preference, the pre-sintering in step (1) is pressureless sintering, and the process parameters are: pre-sintering temperature of 1500° C., pre-sintering time of 1 hour, sintering atmosphere of nitrogen, and vacuum degree of 0.7 KPa.

[0019] As a further preference, the sintering process parameters of step (2) are: sintering pressure 30MPa-40MPa, sintering temperature 1700°C-1750°C, sintering time 10min, sintering atmosphere nitrogen, and vacuum degree 0.7Kpa.

[0020] Beneficial effects of the present invention:

[0021] 1. The present invention selects titanium nitride with excellent mechanical properties as the coating layer, which can effectively increase the resistance to crack expansion and improve the energy dissipation capacity of the composite material. The thin and uniform network continuous layer overcomes the technical problem of introducing more defects due to local agglomeration when introducing the added phase, and at the same time optimizes the fracture toughness and bending strength of the ceramic, which are a pair of contradictory mechanical properties.

[0022] 2. The present invention uses a sintering aid combination of Al2O3 and Y2O3 as an intermediate layer to ensure that the high melting point additive phase and the silicon nitride matrix can be densified at a lower temperature and promote the phase transformation of β-Si3N4.

[0023] 3. The titanium nitride selected in the present invention is a reinforcing phase with excellent electrical conductivity. By connecting it into a uniform three-dimensional network structure as the second coating layer, the boundaries of the two silicon nitride spheres are relatively uniform, close to a line, and the junctions of the three silicon nitride spheres are mostly in a herringbone shape. This solves the technical problem that a conventional dispersed point distribution structure usually requires a high content of conductive filler to break through the conductive threshold, and also deteriorates the mechanical properties of the ceramic.

[0024] 4. The present invention successfully prepares ceramics with a uniform three-dimensional network structure through a dry mixing process and SPS sintering technology, which solves the technical problems of uneven distribution of the network structure prepared by a wet mixing process and a relatively complex preparation process, and improves the possibility of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figures 1 to 5 They are scanning electron microscope photographs of the surface network morphology of the uniform three-dimensional network structure silicon nitride-based composite materials obtained in Examples 1-5 of the present invention after polishing.

[0027] Figure 6 This is a scanning electron microscope picture of the uniform three-dimensional network structure silicon nitride-based composite material obtained in Example 2 of the present invention, in which a crack is deflected after being blocked by a hard network.

[0028] Figure 7 , Figure 8 , Fig. 9 and Fig.10 They are respectively a fracture toughness curve graph, a bending strength curve graph, a hardness curve graph and a conductivity curve graph of the uniform three-dimensional network structure silicon nitride-based composite material obtained in Examples 1-4 of the present invention. DETAILED DESCRIPTION

[0029] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the embodiments of the present invention and the accompanying drawings of the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The silicon nitride core-shell coated powder provided by the present invention has a double-layer structure, with silicon nitride as a matrix, a sintering aid as a first coating layer, and titanium nitride coated on the surface of the sintering aid by dry mixing as a second coating layer.

[0031] In the present invention, the mass ratio of titanium nitride to silicon nitride having the first coating layer is 5-30:70-95. The amount of titanium nitride added has a direct impact on the electrical conductivity of the ceramic. Preferably, the mass ratio of titanium nitride to silicon nitride having the first coating layer is 10:90, and the electrical conductivity of the ceramic is the largest. As the amount of titanium nitride increases, the electrical conductivity of the ceramic begins to decrease, and the mechanical properties also decrease.

[0032] In the present invention, the mass ratio of the silicon nitride to the sintering aid is 95:5.

[0033] In the present invention, the median diameter of the silicon nitride is 75 μm, and the average diameter of the titanium nitride is 50 nm.

[0034] In the present invention, the sintering aid is composed of Al2O3 and Y2O3 in a mass ratio of 2:3. The sintering aid combination and the intermediate layer ensure that the high melting point additive phase and the silicon nitride matrix can be densified at a lower temperature and promote the phase transformation of β-Si3N4. 50 =100nm, purity 99.0%) and Y2O3(d 50 =100nm, purity 99.0%), Al2O3 and Y2O3 in the examples were purchased from Luoyang Zhongchao New Materials Co., Ltd., China.

[0035] The present invention also provides a method for preparing a ceramic block by sintering silicon nitride core-shell coated powder. The silicon nitride powder with a double-layer coating structure is sintered and pressed, and titanium nitride forms a uniform three-dimensional network structure, isolating silicon nitride spheres, and the boundaries of the titanium nitride three-dimensional network are relatively uniform, thereby obtaining a ceramic with a uniform three-dimensional network structure.

[0036] The present invention also provides a method for preparing a ceramic with a uniform three-dimensional network structure, comprising the following steps:

[0037] (1) dry-mixing the spray-dried spherical silicon nitride powder with a sintering aid and pre-sintering the mixture to obtain a silicon nitride matrix powder having a first coating layer;

[0038] (2) dry-mixing the titanium nitride powder with the silicon nitride matrix powder having the first coating layer obtained in step (1) to obtain the silicon nitride matrix powder having the second coating layer;

[0039] (3) Sintering the silicon nitride matrix powder having the second coating layer obtained in step (2).

[0040] In the present invention, the process parameters of dry mixing in step (1) and step (2) are: rotation speed 80-100rpm, mixing time 8-12h. When the amount of TiN added is large, the coating time increases accordingly. For example, when the amount of TiN added is small, the coating can be completed at a rotation speed of 80rpm and a mixing time of 8h. Preferably, the rotation speed is 80rpm and the mixing time is 12h. The pre-sintering in step (1) is pressureless sintering, and the process parameters are: pre-sintering temperature 1500℃, pre-sintering time 1h, sintering atmosphere is nitrogen, and vacuum degree is 0.7Kpa.

[0041] In the present invention, the sintering process parameters of step (2) are: sintering pressure 30MPa-40MPa, sintering temperature 1700℃-1750℃, sintering time 10min, sintering atmosphere nitrogen, vacuum degree 0.7Kpa. Preferably, the sintering pressure is 40Mpa and the sintering temperature is 1750℃.

[0042] The present invention uses a universal testing machine to perform three-point bending and SENB method to test the bending strength, fracture toughness and hardness of the material. The universal testing machine model is DF-7000-MUGP (Golden Testing Machine (Dongguan) Co., Ltd., China). The bending strength of the sample is measured by the three-point bending method. The sample is processed into 20×3×4mm 3 The size of the indenter is set to 16 mm, and the loading speed of the indenter is maintained at 0.5 mm min -1 The SENB method was used to test the toughness of the sample, and the sample size was 20×2×4mm. 3 The slot depth is 2 mm, the span is set to 16 mm, and the loading speed of the indenter is maintained at 0.05 mm min -1 The present invention adopts the four-point probe method (RTS-9, Guangzhou Four Probe Technology Co., Ltd.) to measure the conductivity, and the probe spacing is 1.59 mm. All samples are cut into strips (4×2×10mm 3 ), the sample surface is well polished to ensure good electrical contact during measurement.

[0043] Example 1

[0044] A method for preparing a silicon nitride ceramic having a uniform three-dimensional network structure comprises the following steps:

[0045] (1) By mass percentage, 95% of the spherical silicon nitride powder (particle size d 50=75μm), and 5% well-dispersed sintering aid powder (Al2O3: Y2O3 = 2: 3) were dry mixed in a three-dimensional mixer for 12 hours at a speed of 80rpm, so that the sintering aid was evenly coated on the surface of the silicon nitride microspheres. The coated powder was pre-sintered without pressure at 1500℃ (with nitrogen as the protective gas), so that the sintering aid melted and evenly adhered to the surface of the silicon nitride microspheres to form the first coating layer;

[0046] (2) dry-mixing titanium nitride powder (average diameter of 50 nm) in a mass ratio of 5:95 and the silicon nitride matrix coating powder obtained in step (1) in a three-dimensional mixer for 12 h at a rotation speed of 80 rpm to form a second coating layer, thereby obtaining a silicon nitride core-shell coated powder having a double-layer coating structure;

[0047] (3) The mixed powder obtained in step (2) is sintered at 1750° C. for 10 min using SPS (spark plasma sintering), the sintering pressure is 40 MPa, the protective gas is nitrogen, and the vacuum degree is 0.7 KPa. Finally, the sintered sample is cooled, demolded, and polished to obtain a ceramic with a uniform three-dimensional network structure.

[0048] See also Figure 1 After SPS sintering and polishing, silicon nitride ceramics have a uniform three-dimensional network structure.

[0049] See also Figure 7 , Figure 8 , Fig. 9 and Fig.10 After testing, the conductivity of the ceramic obtained in Example 1 is 1.72*10 3 S / m, the material bending strength is about 807MPa, and the fracture toughness is 6.85MPa·m 1 / 2 , hardness is 15.23GPa.

[0050] Example 2

[0051] A method for preparing a ceramic having a three-dimensional network structure coating layer comprises the following steps:

[0052] (1) By mass percentage, 95% of the spherical silicon nitride powder (particle size d 50 =75μm), and 5% well-dispersed sintering aid powder (Al2O3: Y2O3 = 2: 3) were dry mixed in a three-dimensional mixer for 12 hours at a speed of 80rpm, so that the sintering aid was evenly coated on the surface of the silicon nitride microspheres. The coated powder was pre-sintered without pressure at 1500℃ (with nitrogen as the protective gas), so that the sintering aid melted and evenly adhered to the surface of the silicon nitride microspheres to form the first coating layer;

[0053] (2) dry-mixing titanium nitride powder (average diameter of 50 nm) in a mass ratio of 10:90 with the silicon nitride matrix coating powder obtained in step (1) in a three-dimensional mixer for 12 h at a rotation speed of 80 rpm to form a second coating layer, thereby obtaining a silicon nitride core-shell coated powder having a double-layer coating structure;

[0054] (3) The mixed powder obtained in step (2) is sintered at 1750° C. for 10 min using SPS (spark plasma sintering), the sintering pressure is 40 MPa, the protective gas is nitrogen, and the vacuum degree is 0.7 KPa. Finally, the sintered sample is cooled, demolded, and polished to obtain a ceramic with a uniform three-dimensional network structure.

[0055] See also Figure 2 After SPS sintering and polishing, silicon nitride ceramics have a uniform three-dimensional network structure. Figure 6 In the network structure silicon nitride-based composite material obtained in Example 2, cracks are deflected after being blocked by the hard network. Figure 8 and Fig. 9 The ceramic material of Example 2 has a bending strength of 726.61 MPa and a fracture toughness of 7.91 MPa·m 1 / 2 , hardness 14.14GPa. Fig.10 , after the conductivity test, the ceramic conductivity is 1.07*10 4 S / m.

[0056] Example 3

[0057] A method for preparing a ceramic having a three-dimensional network structure coating layer comprises the following steps:

[0058] (1) By mass percentage, 95% of the spherical silicon nitride powder (particle size d 50 =75μm), and 5% well-dispersed sintering aid powder (Al2O3: Y2O3 = 2: 3) were dry mixed in a three-dimensional mixer for 12 hours at a speed of 80rpm, so that the sintering aid was evenly coated on the surface of the silicon nitride microspheres. The coated powder was pre-sintered without pressure at 1500℃ (with nitrogen as the protective gas), so that the sintering aid melted and evenly adhered to the surface of the silicon nitride microspheres to form the first coating layer;

[0059] (2) dry mixing titanium nitride powder (average diameter of 50 nm) in a mass ratio of 15:85 and the silicon nitride matrix coating powder obtained in step (1) in a three-dimensional mixer for 12 hours at a rotation speed of 80 rpm to form a second coating layer, thereby obtaining a silicon nitride core-shell coated powder having a double-layer coating structure;

[0060] (3) The mixed powder obtained in step (2) is sintered at 1750° C. for 10 min using SPS (spark plasma sintering), the sintering pressure is 40 MPa, the protective gas is nitrogen, and the vacuum degree is 0.7 KPa. Finally, the sintered sample is cooled, demolded, and polished to obtain a ceramic with a uniform three-dimensional network structure.

[0061] See also Figure 3 After SPS sintering and polishing, silicon nitride ceramics have a uniform three-dimensional network structure. Figure 7 , Figure 8 , Fig. 9 and Fig.10 The silicon nitride ceramic with a uniform three-dimensional network structure obtained in Example 3 has a hardness of 14 GPa and a fracture toughness of 7.55 MPa·m 1 / 2 , the bending strength is 707.41MP and the electrical conductivity is 794S / m.

[0062] Example 4

[0063] A method for preparing a ceramic having a three-dimensional network structure coating layer comprises the following steps:

[0064] (1) By mass percentage, 95% of the spherical silicon nitride powder (particle size d 50 =75μm), and 5% well-dispersed sintering aid powder (Al2O3: Y2O3 = 2: 3) were dry mixed in a three-dimensional mixer for 12 hours at a speed of 80rpm, so that the sintering aid was evenly coated on the surface of the silicon nitride microspheres. The coated powder was pre-sintered without pressure at 1500℃ (with nitrogen as the protective gas), so that the sintering aid melted and evenly adhered to the surface of the silicon nitride microspheres to form the first coating layer;

[0065] (2) dry-mixing titanium nitride powder (average diameter of 50 nm) in a mass ratio of 20:80 with the silicon nitride matrix coating powder obtained in step (1) in a three-dimensional mixer for 12 h at a rotation speed of 80 rpm to form a second coating layer, thereby obtaining a silicon nitride core-shell coated powder having a double-layer coating structure;

[0066] (3) The mixed powder obtained in step (2) is sintered at 1750° C. for 10 min using SPS (spark plasma sintering), the sintering pressure is 40 MPa, the protective gas is nitrogen, and the vacuum degree is 0.7 KPa. Finally, the sintered sample is cooled, demolded, and polished to obtain a ceramic with a uniform three-dimensional network structure.

[0067] See also Figure 4 After SPS sintering and polishing, silicon nitride ceramics have a uniform three-dimensional network structure. Figure 7 , Figure 8 , Fig. 9 and Fig.10 The silicon nitride ceramic with a uniform three-dimensional network structure obtained in Example 4 was tested to have a hardness of 13.81 GPa and a fracture toughness of 7.07 MPa·m 1 / 2 , bending strength is 592MP and electrical conductivity is 657S / m.

[0068] Example 5

[0069] A method for preparing a ceramic having a three-dimensional network structure coating layer comprises the following steps:

[0070] (1) By mass percentage, 95% of the spherical silicon nitride powder (particle size d 50 =75μm), and 5% well-dispersed sintering aid powder (Al2O3: Y2O3 = 2: 3) were dry mixed in a three-dimensional mixer for 12 hours at a speed of 80rpm, so that the sintering aid was evenly coated on the surface of the silicon nitride microspheres. The coated powder was pre-sintered without pressure at 1500℃ (with nitrogen as the protective gas), so that the sintering aid melted and evenly adhered to the surface of the silicon nitride microspheres to form the first coating layer;

[0071] (2) dry mixing titanium nitride powder (average diameter of 50 nm) in a mass ratio of 30:70 and the silicon nitride matrix coating powder obtained in step (1) in a three-dimensional mixer for 8 hours at a rotation speed of 100 rpm to form a second coating layer, thereby obtaining a silicon nitride core-shell coated powder having a double-layer coating structure;

[0072] (3) The mixed powder obtained in step (2) is sintered at 1700° C. for 10 min using SPS (spark plasma sintering), the sintering pressure is 30 MPa, the protective gas is nitrogen, and the vacuum degree is 0.7 KPa. Finally, the sintered sample is cooled, demolded, and polished to obtain a ceramic with a uniform three-dimensional network structure.

[0073] See also Figure 5 After SPS sintering and polishing, silicon nitride ceramics have a uniform three-dimensional network structure. Figure 7 , Figure 8 , Fig. 9 and Fig.10 The silicon nitride ceramic with a uniform three-dimensional network structure obtained in Example 5 was tested to have a hardness of 12.53 GPa and a fracture toughness of 6.48 MPa·m 1 / 2 , bending strength is 498.78MP and electrical conductivity is 310S / m.

[0074] Comparative Example

[0075] The method for preparing silicon nitride ceramics comprises the following steps:

[0076] (1) By mass percentage, 95% of the spherical silicon nitride powder (particle size d 50 =75μm), and 5% well-dispersed sintering aid powder (Al2O3: Y2O3 = 2: 3) were dry mixed in a three-dimensional mixer for 12 hours at a speed of 80rpm, so that the sintering aid was evenly coated on the surface of the silicon nitride microspheres. The coated powder was pre-sintered without pressure at 1500℃ (with nitrogen as the protective gas), so that the sintering aid melted and evenly adhered to the surface of the silicon nitride microspheres to form a unique coating layer;

[0077] (2) The mixed powder obtained in step (1) was sintered at 1750° C. for 10 min using SPS (spark plasma sintering), with a sintering pressure of 40 MPa, a protective gas of nitrogen, and a vacuum degree of 0.7 KPa. Finally, the sintered sample was cooled, demolded, and polished.

[0078] The conductivity of the ceramic obtained in the comparative example is 3.16*10 -9 S / m.

[0079] Compared with Examples 1-5, the comparative example does not add titanium nitride, and sintering is performed after the sintering aid is coated on the surface of silicon nitride. Comparison between Examples 1-5 and the comparative example shows that adding titanium nitride can increase the electrical conductivity of the ceramic.

[0080] Beneficial effects of the present invention:

[0081] 1. The present invention selects titanium nitride with excellent mechanical properties as the coating layer, which can effectively increase the resistance to crack expansion and improve the energy dissipation capacity of the composite material. The thin and uniform network continuous layer overcomes the technical problem of introducing more defects due to local agglomeration when introducing the added phase, and optimizes the fracture toughness and bending strength of the ceramic, which are a pair of contradictory mechanical properties.

[0082] 2. The present invention uses a sintering aid combination of Al2O3 and Y2O3 as an intermediate layer to ensure that the high melting point additive phase and the silicon nitride matrix can be densified at a lower temperature and promote the phase transformation of β-Si3N4.

[0083] 3. The titanium nitride selected in the present invention is a reinforcing phase with excellent electrical conductivity. By connecting it into a uniform three-dimensional network structure as the second coating layer, the technical problem that a higher content of conductive filler is usually required to break through the conductive threshold in the conventional dispersed point distribution structure and the mechanical properties of the ceramic are also deteriorated is solved.

[0084] 4. The present invention successfully prepares ceramics with a uniform three-dimensional network structure through a dry mixing process and SPS sintering technology, which solves the technical problems of uneven distribution of the network structure prepared by a wet mixing process and a relatively complex preparation process, and improves the possibility of industrial production.

[0085] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. Silicon nitride core-shell coated powder, characterized in that: The silicon nitride powder has a double-layer structure, with silicon nitride as a matrix, a sintering aid as a first coating layer, and titanium nitride coated on the surface of the sintering aid by dry mixing as a second coating layer.

2. The silicon nitride core-shell coated powder according to claim 1, characterized in that: The mass ratio of the titanium nitride to the silicon nitride having the first coating layer is 5-30:70-95.

3. The silicon nitride with a coating layer according to claim 2, characterized in that: The mass ratio of the titanium nitride to the silicon nitride having the first coating layer is 10:

90.

4. The silicon nitride core-shell coated powder according to claim 1, characterized in that: The mass ratio of the silicon nitride to the sintering aid is 95:

5.

5. The silicon nitride core-shell coated powder according to claim 1, characterized in that: The sintering aid is composed of Al2O3 and Y2O3 in a mass ratio of 2:

3.

6. A ceramic prepared from silicon nitride core-shell coated powder as claimed in claim 1, characterized in that: The silicon nitride powder with the coating layer is prepared by sintering.

7. The method for preparing ceramics according to claim 6, characterized in that: The steps include: (1) dry-mixing the spray-dried spherical silicon nitride powder with a sintering aid and then pressurelessly sintering the mixture to obtain a silicon nitride matrix powder having a first coating layer; (2) dry-mixing the titanium nitride powder with the silicon nitride matrix powder having the first coating layer obtained in step (1) to obtain the silicon nitride matrix powder having the second coating layer; (3) Sintering the silicon nitride matrix powder having the second coating layer obtained in step (2).

8. The preparation method according to claim 7, characterized in that: The process parameters of dry mixing in step (1) and step (2) are: rotation speed 80-100 rpm, mixing time 8-12 h.

9. The preparation method according to claim 8, characterized in that: The pre-sintering in step (1) is pressureless sintering, and the process parameters are: pre-sintering temperature 1500°C, pre-sintering time 1 h, sintering atmosphere nitrogen, and vacuum degree 0.7 KPa.

10. The preparation method according to claim 8, characterized in that: The sintering process parameters of step (2) are: sintering pressure 30 MPa-40 MPa, sintering temperature 1700°C-1750°C, sintering time 10 min, sintering atmosphere nitrogen, and vacuum degree 0.7 Kpa.

Citation Information

Patent Citations

  • Method for preparing high porosity silicon nitride ceramic based on laser selective sintering

    CN110330344A

  • Improved performance of technical ceramics

    CN110382440A

  • Silicon nitride-based textured gradient material as well as preparation method and application thereof

    CN114835501A

  • Layered composite ceramic cylindrical roller and preparation method thereof

    CN115124353A

  • Prepn of nano titanium nitride-silicon nitride composite material

    CN1417163A